Application of Polyethylene Glycol Immobilized Clostridium sp. LS2 for Continuous Hydrogen Production From Palm Oil Mill Effluent in Upflow Anaerobic Sludge Blanket Reactor - Singh, Lakhveer; Muhammad Faisal, Siddiqui; Anwar, Ahmad; Mohd Hasbi, Ab. Rahim; Mimi Sakinah, A. M.; Zularisam, A. W. (Elsevier Ltd, 2013)
A novel polyethylene glycol (PEG) gel was fabricated and used as a carrier to immobilize Clostridium sp. LS2 for continuous hydrogen production in an upflow anaerobic sludge blanket (UASB) reactor. Palm oil mill effluent (POME) was used as the substrate carbon source. The optimal amount of PEG-immobilized cells for anaerobic hydrogen production was 12% (w/v) in the UASB reactor. The UASB reactor containing immobilized cells was operated at varying hydraulic retention times (HRT) that ranged from 24 to 6 h at 3.3 g chemical oxygen demand (COD)/L/h organic loading rate (OLR), or at OLRs that ranged from 1.6 to 6.6 at 12 h HRT. The best volumetric hydrogen production rate of 336 mL H2/L/h (or 15.0 mmol/L/h) with a hydrogen yield of 0.35 L H2/g CODremoved was obtained at a HRT of 12 h and an OLR of 5.0 g COD/L/h. The average hydrogen content of biogas and COD reduction were 52% and 62%, respectively. The major soluble metabolites during hydrogen fermentation were butyric acid followed by acetic acid. It is concluded that the PEG-immobilized cell system developed in this work has great potential for continuous hydrogen production from real wastewater (POME) using the UASB reactor.